Cosmopolitanism and Decolonization: Contradictory Perspectives on School Reform to Advance Reconciliation with Indigenous Peoples - Wotherspoon, Terry; Milne, Emily (International Journal for Talent Development and Creativity, 2022)
Canadian school jurisdictions have taken steps to accommodate objectives to advance cosmopolitan education reflecting principles such as global citizenship, compassion, tolerance, responsibility, and respect within school curricula and educational practice. At the same time, a parallel set of reconciliation-related educational reforms, aligned with the Calls to Action that accompanied the 2015 Truth and Reconciliation Commission final report, have also gained urgency. Elements of reconciliation processes complement visions of cosmopolitanism, including objectives to foster dialogue and understanding between groups and advancements towards more holistic orientations to pedagogy and knowledge. However, conceptually and in practice, several tensions emerge, especially in a context in which educational priorities are contested. In this paper, we explore these connections and tensions with reference to findings from our research examining public perspectives on educational reforms to support reconciliation.